Use of portfolio-based learning and assessment in community-based field curriculum - Sahu Swaroop; Soudarssanane M; Roy Gautam; Premrajan K; Sarkar Sonali (Wolters Kluwer Medknow Publications, 2008)
Portfolio-based learning is recognized in medical education. It helps students to assess themselves as per the key learning objectives and outcomes expected out of them. The faculty could also get feedback regarding individual student′s progress toward learning outcomes and facilitate the students achieve the same. This article addresses the process of portfolio development and assesses from students feedbacks, if portfolio-based learning is an improvement over record-based study in community-based field studies. The results of this study shows that involving students in framing objectives, developing a mechanism for self-introspection and self-assessment by the students and a mechanism by which faculty can monitor each student′s progress toward the defined objectives can significantly enhance the learnability of the students.